Commercial shipping handbook - Brodie, Peter R., 1947- (Routledge, 2015)
The Commercial Shipping Handbook is an invaluable reference tool for anyone involved in international trade and a first step towards understanding the framework within which the international movement of goods by sea is conducted. The handbook gives concise explanations of the many activities that comprise shipping, explaining the terms and how they interrelate.